The influence of a color themed HMI on trust and take-over performance in automated vehicles - el Jouhri, Aboubakr; el Sharkawy, Ashraf; Paksoy, Hakan; Youssif, Omar; He, Xiaolin; Kim, Soyeon; Happee, Riender (Frontiers in Psychology, 2023)
SAE Level 3 is known as conditional driving automation. As long as certain conditions are met, there is no need to supervise the technology and the driver can engage in non-driving related tasks (NDRTs). However, a human driver must be present and alert to take over when the automation is facing its system limits. When such an emergency takes place, the automation uses the human machine interface (HMI) to send a take-over request (TOR) to the driver. We investigated the influence of a colour themed HMI on the trust and take-over performance in automated vehicles. Using a driving simulator, we tested 45 participants divided in 3 groups with a baseline auditory HMI and two advanced colour themed HMIs consisting of a display and ambient lighting with the colours red and blue. Trust in automation was assessed using questionnaires while take-over performance was assessed through response time and success rate. Compared to the baseline HMI, the colour themed HMI is more trustworthy and participants understood their driving tasks better. Results show that the colour themed HMI is perceived as more pleasant compared to the baseline HMI and leads to shorter reaction times. Red ambient lighting is seen as more urging than blue but HMI colour did not significantly affect the general HMI perception and TOR performance.